The Burden, the Craving, the Tool. The Provisioning of the 10th Century Byzantine Army in the Light of Leo’s Tactica and Sylloge Tacticorum - Wierzbiński, Szymon (Studia Ceranea, 2020)
It seems obvious that 10th century was a period in which the Byzantine polemology flourished once again, before it collapsed one hundred years later. During that period numerous authors of Byzantine military treaties instructed imperial commanders how to wage war. Among many issues organization of the campaign was always an important aspect. In this paper I will try to clarify selected problems. First, I will try to specify what the soldiers ate on a daily basis. Next, I will determine to what extent the provisioning system met the expectations and needs of the Byzantines fighting for the empire. With the help of Tactica and Sylloge Tacticorum, I will try to explain how the rations were gathered, transported and protected. Finally, I will specify how the supplies were utilized not only as a means of nourishment, but also as a tool of war. The following research was carried out on the basis of military treaties from the 10th century, since this time was the peak of Byzantine military revival. Although I mainly base my research on the work of Leon the Wise and the anonymous treaty known as Sylloge Tacticorum, I also occasionally refer to other works, such as Peri Strategias, De velitatione and Praecepta Militaria.